Faktor-faktor yang berhubungan dengan status anemia pada remaja putri di Kampung Cariu Tangerang - Syifa Hana Fauziyah; Nur Setiawati Rahayu (UHAMKA PRESS, 2021)
Anemia is an indicator of poor health status. Anemia attacks a half billion of fertile women in the world and it is a nutritional problem that affects millions of people in various developing countries. Many factors that lead to anemia, some factors among them are intake of protein, vitamin C, vitamin B12, and iron, knowledge related to anemia and menstrual period. The purpose of this research was to analyze the relationship between intake of protein, vitamin C, vitamin B12, and iron, the knowledge about anemia, and menstruation to anemia status in adolescent girls in Kampung Cariu, Desa Tobat, Kecamatan Balaraja, Kabupaten Tangerang. The quantitative methodology used was cross sectional. The data taken in this research were hemoglobin levels, intake of protein, vitamin C, vitamin B12, and iron using the SQ-FFQ form, the knowledge about anemia and menstruation using a questionnaire. The sampling technique in this study was total sampling (44 subjects). The results showed there was a relationship between vitamin C intake and anemia status and there were no relationships between intake of protein, vitamin B12, iron, the knowledge about anemia, and menstruation with anemia status among young women in Kampung Cariu.